Employee Digital Transformation Experience Towards Automation Versus Augmentation: Implications for Job Attitudes - Ren, Shuang; Chowdhury, Soumyadeb (Human Resource Management, 2025)
ABSTRACT As a growing number of organizations are leveraging emerging technologies to optimize their operations to stay competitive, digital transformation has fast become an integral part of employee experience at the intersection of their psychological states and the workplace. However, employee experience with digital transformation is heterogeneous given the different approaches organizations take toward this initiative. We hence simultaneously consider both the nature of the digital transformation (i.e., automation versus augmentation) and the presence versus absence of employee voice mechanisms. Drawing from psychological reactance theory, we argue that employee experience of automation‐driven transformation will be more likely to engender psychological reactance, which in turn impacts important employee job attitudes, represented by job satisfaction, employment security, and turnover intention. We also argue that employee voice moderates this mediated relationship. Using data from two studies with different samples and research designs (an experimental design in Study 1 and a field survey in Study 2), the findings support our hypothesized relationships. The two‐study approach helps to enhance the validity of the research and demonstrate the generalizability of findings, thereby strengthening our contributions to the literature. Overall, the studies theoretically extend understandings of how employees respond to digital transformation by offering new insights into the psychological reactance mechanism. We also provide practical implications for business and practitioners seeking to manage digital transformation in ways that enhance desired employee job attitudes.